Vaccination coverage in the context of the emerging Yellow Fever threat in French Guiana. - Claude Flamand; Sarah Bailly; Camille Fritzell; Sandrine Fernandes Pellerin; Alhassane Toure; Naïssa Chateau; Mona Saout; Sébastien Linares; Fabien Dubois; Laurent Filleul; Mirdad Kazanji (Public Library of Science (PLoS), 2019)
Background French Guiana, a French overseas department located in South America between Brazil and Surinam, is the only European territory geographically located in the Amazonian forest complex and is considered endemic for yellow fever (YF). In the context of the emergent threat of YF in Latin America, we conducted a large household cross-sectional survey from June to October 2017 to estimate vaccination coverage in the population and to determine associations with sociodemographic and geographical characteristics. Methodology/principal findings In total, 1,415 households and 2,697 individuals were included from the 22 municipalities of French Guiana. YF vaccination coverage was estimated at 95.0% (95% CI: 93.4-96.2) in the entire territory but was spatially heterogeneous, with the lowest levels estimated in the western part of the territory along the Surinamese cross-border region, particularly in children under 16 years who were not enrolled in school, immigrant adults and disadvantaged populations with low socioeconomic indexes. Conclusions/significance Despite the good vaccination coverage against YF in the general population of French Guiana resulting from the compulsory nature of YF vaccination for residents and travelers, there is an urgent need to improve vaccination coverage in vulnerable populations living in the northwestern part of the territory to limit the risk of transmission in the context of the emerging YF threat in South America. Despite the relative rarity of YF and the significant number of infectious and tropical diseases in French Guiana, clinicians should adopt a high index of suspicion for YF, particularly in vulnerable and at-risk populations.